A novel approach for verifying selective user identity attributes online using open banking APIs. Issue 5 (4th July 2022) - Pete, Amogh; Gupta, Himanshu; Varshney, Shubham; Chandra, Pushpendra Kumar; Negi, Satish Kumar
Abstract: In this work, we propose a novel workflow to tackle the problem of verifying individuals' identities online assuming banks as a central source of truth. The existing process for this involves auth mechanisms from privately held companies, where the data do not have any physical backing by an authorized entity, reducing its credibility. Alongside, the online verification methods used are unsophisticated, like passwords and OTPs, and anyone can easily impersonate with access to one's devices and credentials. Considering alternatives like national identity cards to prove data, one needs to verify original documents again and again physically, decreasing customer's inspiration for the activity. One more issue to tackle is excessive data getting shared during authentication can serve maliciously against the users. Companies utilize this data for digital profiling of users and targeting advertisements. Hence, only data attributes of utmost necessity should get shared. We have tried to create a web app named Canfirm to demonstrate the possibilities, workflow and use of open banking APIs.